Pe Pengaruh Layanan Informasi Menggunakan Media Powerpoint Untuk Meningkatkan Motivasi Belajar Siswa Kelas X SMAN 5 Kota Bengkulu: Pendahuluan, Metode Penelitian, Hasil Penelitian dan Pembahasan, Kesimpulan, Daftar Pustaka - Muhammad Aiwa Adi Darma; Rita Sinthia; Arsyadani Mishbahuddin (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2024)
This study aimed to determine the effect of information services using powerpoint media to increase student learning motivation using the experimental method of one group pretest-posttest design. The population in this study were all class X students totaling 432 students with a sample of 36 students determined using purposive sampling technique. The average score before the information service treatment using powerpoint media was 105 with a medium category after being treated, the average score increased to 123. The data analysis technique uses a t-test (paired sample t-test) which is indicated by a value of t = -10,599 with a significant (2-tailed) of 0.000 (P <0.05) which means that there is an effect of information services using powerpoint media to increase student learning motivation. Keywords: learning motivation, information services, powerpoint